Eksplorasi Persepsi Siswa Sekolah Dasar dalam Pembelajaran Huruf Hijaiyah Berbasis Permainan - Qutby, Hurriatus Tsaniyah; Ulfa, Saida; Nasih, Achmad Munjin (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2021)
In this digital era, children are more interested in playing games on their smartphones until the phenomenon of game addiction arises, rather than having to read Iqro let alone the Qur’an. Researchers aimed to determine the perception of the use of mobile game base learning in learning hijaiyah letters. In this study using a quantitative method with a descriptive approach. The technique used in data collection uses survey techniques through questionnaires. The questionnaire was developed using TAM (Technology Acceptance Model). Based on the results obtained, the usefulness and ease of mobile game-based learning hijaiyah is believed to improve the ability to read hijaiyah letters and be acceptable to respondents. Respondents intend to reuse mobile game based learning in the future. This research can be a reference or contribution about TAM (Technology Acceptance Model) on using mobile game based learning hijaiyah.